Analyzing the revenue condition of “IFAD AUTOS LTD” based on the performance of financial activities and studying the impact of COVID-19 on the company’s performance - Chakrabarty, Binayak (Brac University, 2021)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2021.